I Am a Boy or a Girl: Discrimination in Gender Relations and Sexuality in Early Childhood Education (Research, Society and Development, 2019)
With this scientific investigation we aimed to understand if the children, in the phase previous to the Complex of Oedipus, evidences discriminations in the relations of genera and sexuality that indicates the way of being girl or boy. Following the type of action research, we look for elements present in the teachers' discourses and alternatives for the understanding of pedagogical impasses. The following methods were used: inductive and case study; because the problem was investigated from the intended objectives. The techniques of data collection were through interviews with structured topics with questions open to teachers, and student observation. To analyze the data, a qualitative interpretative approach was adopted in a discussion of the empirically obtained data interpreting its results with the contributions of theoretical authors. The result of this investigation was the one where the children showed discrimination in the relations of gender and sexuality after the third and fourth year of life, leaving this evident in the observation of their behavior, in the relationships they establish and in the teacher's eyes. It is concluded that in addition to the taboo, the resistance, and the lack of control over the subject, there are difficulties to find theoretical and methodological alternatives to deal with these themes with coherence, without trauma and without prejudice, because they demonstrate an adultcentric and heteronormative understanding.